ENHANCING PURCHASE DECISIONS IN RETAIL INDUSTRY: VISUAL MERCHANDISE AND HEDONIC SHOPPING MOTIVATION'S ROLE - Hafizah, Qonita Amalia; Sari, Puspa Novita (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
In an increasingly competitive retail world, understanding the factors that influence consumer purchasing decisions is key to business success. Visual merchandising and hedonic shopping motivation are two important factors that are often overlooked but have a significant impact on consumer behavior. Visual merchandising refers to the use of visual elements such as product layout, lighting, and displays to attract consumer attention and create an engaging shopping experience. Meanwhile, hedonic shopping motivation reflects the consumer's drive to shop for pleasure and positive emotional experiences, not just to fulfill functional needs. This study aims to investigate the influence of visual merchandising and hedonic shopping motivation on purchase decisions, with impulse buying serving as an intervening (mediating) variable. The research adopts a quantitative approach, with a sample size of 190 respondents. The sampling method used in this study is purposive sampling. Data collection was conducted through the distribution of questionnaires both directly (offline) and indirectly (online) using a semantic differential scale. Data analysis was carried out using the SEM-PLS method, with data processing performed using SMART PLS 3.0 software. The results of the study indicate that three out of five proposed hypotheses can be accepted. The findings reveal that visual merchandising does not influence impulse buying and purchase decisions, hedonic shopping motivation has a positive and significant effect on impulse buying and purchase decisions, and impulse buying has a positive and significant effect on purchase decisions.